دور السياحة العلاجية في التنمية السياحية المحلية - دراسة حالة الأردن- - التجاني سميرة; دفرور عبد النعيم (جامعة الوادي University of Eloued, 2024)
تهدف هذه الدراسة إلى تقديم واقع السياحة العلاجية في الأردن كتجربة رائدة وسابقة مقارنة ببقية الدول العربية، من خلال معرفة دورها الرئيسي في كيفية المساهمة في تنمية السياحة المحلية لها، ومعرفة كيفية لاستخدام الموارد الطبية والطبيعية المتاحة لتحقيق أهدافها، حيث تم اعتماد المنهج الوصفي التحليلي لتسليط الضوء على دور السياحة العلاجية في تنمية السياحة المحلية في الأردن والأهداف التي تسعى إليها لتطوير الخدمات الطبية وبنيتها التحتية، وقد خلصنا إلى أن هناك عدة مقومات للسياحة العلاجية ساهمت في نجاح التنمية المحلية وتحسين الاقتصاد الأردني، وتطوير البنية التحتية للقطاع الصحي وتعزيز جودة الخدمات المقدمة، والعناية بالمعالم الأثرية التي تشكل مصدر استقطاب. للسياح المحليين والأجانب، حيث يسعى الأردن إلى وضع عدة استراتيجيات لتنمية الوعي السياحي لدى مجتمعه والنهوض بهذا القطاع. This study aims to provide the reality of medical tourism in Jordan as a leading and previous experience compared to the rest of the Arab countries, by knowingits main role in how to contribute to the development of local tourism to it, and to know how to use the medical and natural resources available to achieveits goals, where the descriptive analytical approach was adopted to highlight On the role of medical tourism in the development of local tourism in Jordan and the goals itseeks to developmedical services and their infrastructure, we have concluded that there are several elements of medical tourism that contributed to the success of local development and improving the Jordanian economy, developing the infrastructure of the healths ector, enhancing the quality of services provided, and caring for landmarks The archaeologicalis a source of polarization. For local and foreign tourists, Jordan seeks to develop several strategies to develop tourisma ware nessamongits community and advancethis sector.
The role of medical tourism in local tourism development - Jordan's case study -
Keywords: سياحة العلاج; المركبات الحموية; التنمية المحلية; التنمية السياحية; السياحة المحلية